Curriculum Theory: The Missing Perspective in Teacher Education for Inclusion. (February 2020) - Pugach, Marleen C.; Blanton, Linda P.; Mickelson, Ann M.; Boveda, Mildred
Our intergenerational authorial team takes up a central—and unresolved—issue within teacher education for inclusion, namely, the role of curriculum in reconceptualizing pre-service programs. We specifically review literature and policy on how special education teacher educators have approached conceptions of curriculum, using this past as prologue to argue that the teacher education curriculum requires a community of educators constructing a balance between a shared equity agenda to support the preparation of all teachers for inclusion, and the simultaneous need to prepare experts who can effectively share and utilize expertise that addresses the specific learning needs of marginalized learners, including those with disabilities. Unless curriculum is addressed comprehensively, deep transformation will be difficult to achieve, and role clarity for prospective special education teachers is likely to remain unclear. Our aim is for readers to consider the complicating power of curriculum theory as essential framework for renegotiating the teacher education curriculum for inclusion.